Novel pyrimidine-1,3,4-oxadiazole hybrids and their precursors as potential antimycobacterial agents - Pflégr, Václav; Stolaříková, Jiřina; Pál, Adrián; Korduláková, Jana; Krátký, Martin (Future medicinal chemistry, 2023)
Background: Molecular hybridization and isostery are proven approaches in medicinal chemistry, and as such we used them to design novel compounds that we investigated as potential antimycobacterials to combat drug-resistant strains. Methods & results: Prepared N-alkyl-2-(pyrimidine-5-carbonyl)hydrazine-1-carboxamides were cyclized to N-alkyl-5-(pyrimidin-5-yl)-1,3,4-oxadiazol-2-amines along with their analogues. A total of 48 compounds were tested against Mycobacterium tuberculosis H37Rv, Mycobacterium avium and Mycobacterium kansasii, with oxadiazoles and C8-C12 alkyls being the most effective from a concentration of 2 μM. Multidrug-resistant strains were inhibited at same concentrations as the susceptible strain. For the most potent N-dodecyl-5-(pyrimidin-5-yl)-1,3,4-oxadiazol-2-amine, the mechanism of action related to cell wall biosynthesis was investigated. Conclusion: Pyrimidine-1,3,4-oxadiazole hybrids are unique antimycobacterial agents inhibiting mainly M. tuberculosis strains without cross-resistance to current drugs and are thus promising drug candidates.
Keywords: Structure-Activity Relationship; Oxadiazoles; Amines; antimycobacterial activity; antibakteriální látky; hydrazinecarboxamides; aminy; Antitubercular Agents; pyrimidiny; antituberkulotika; Microbial Sensitivity Tests; pyrimidine; mikrobiální testy citlivosti; Pyrimidines; 1,3,4-oxadiazole; oxadiazoly; vztahy mezi strukturou a aktivitou; Mycobacterium tuberculosis; Anti-Bacterial Agents